The Impact of Stunting Prevention Content on Parental Caregiving Skills for Early Childhood Development - Krisnaeni; Iriyanto, Tomas; Wuri Astuti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Parental caregiving plays a pivotal role in the growth and development of children. High-quality caregiving ensures that children grow and develop optimally according to their developmental stages. Parenting practices also significantly influence children's nutritional status. The better the parenting skills, the better the nutritional status of the child. Good nutritional status is essential in preventing stunting. Currently, stunting poses a serious threat to Indonesian children, with a prevalence rate of 21.6% in 2022. Therefore, enhancing parental caregiving skills is crucial to ensuring a better quality of life for all Indonesian children. This study aimed to examine the effect of stunting prevention content on parental caregiving skills. A pre-experimental method with a one-group pretest-posttest design was employed in this study, involving 43 participants. Data were analyzed using descriptive statistics and a t-test. The results revealed an improvement in posttest scores compared to pretest scores. Additionally, the t-test analysis showed a significance value of < 0.001 (p < 0.05). These findings indicate that stunting prevention content has a positive impact on the caregiving skills of parents with children aged 0–2 years.